Bioenergy and Breast Cancer: A Report on Tumor Growth and Metastasis. (5th September 2016) - Running, Alice; Greenwood, Mark; Hildreth, Laura; Schmidt, Jade
Abstract : As many as 80% of the 296, 000 women and 2, 240 men diagnosed with breast cancer in the United States will seek out complementary and alternative medicine (CAM) treatments. One such therapy is Healing Touch (HT), recognized by the National Center for Complementary and Integrative Health (NCCIH) as a treatment modality. Using a multiple experimental groups design, fifty-six six- to eight-week-old Balb/c mice were injected with 4T1 breast cancer tumor cells and randomly divided into intervention and positive control groups. Five days after tumor cell injection, mice in the intervention groups received HT either daily or every other day for 10 minutes by one HT practitioner. At 15 days after tumor cell injection, tumor size was measured, and metastasis was evaluated by a medical pathologist after necropsy. Tumor size did not differ significantly among the groups (F ( 3, 52 ) = 0.75, p value = 0.53). The presence of metastasis did not differ across groups (chi-square(3) = 3.902, p = 0.272 ) or when compared within an organ (liver: chi-square(3) = 2.507, p = 0.474 ; lungs: chi-square(3) = 3.804, p = 0.283 ; spleen: chi-square(3) = 0.595, p = 0.898 ). However, these results did indicate a moderate, though insignificant, positive impact of HT and highlight the need for continued research into dose, length of treatment, and measurable outcomes (tumor size, metastasis) to provide evidence to suggest application for nursing care.